Manfaat Pelaksanaan Cek Kesehatan Rutin sebagai Awal Deteksi Dini - Wahyuni, Wahyuni; Lydia Mardison Putri; Ullia Putri Marbun; Mitra Elita (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
According to the World Health Organization (WHO), routine health checks are a crucial part of health promotion strategies, early disease detection, and complication prevention. WHO highlights that non-communicable diseases (NCDs) such as diabetes, hypertension, and heart disease are the leading causes of death globally. Many of these conditions can be prevented or controlled through regular health examinations. This community service activity aimed to increase public awareness of the importance of regular health checks. The implementation method used a “Problem Solving Cycle” approach to identify, analyze, and prioritize health problems, explore root causes, and plan appropriate interventions. The activity took place on Sunday, April 20, 2025, at Pantai Puruih, Padang City. Services included checking vital signs, blood glucose, cholesterol, uric acid levels, and providing health education. Results: The event reached 66 participants with high enthusiasm and active involvement in health screening and consultation. Conclusion: Routine health checks are vital for early detection of NCDs, increasing awareness, and encouraging healthy lifestyles through education and accessible health services.